History and establishment process of relations of contract of package entrepreneurial license (Journal of actual problems of jurisprudence, 2015)
The Treaty of the complex enterprise license (franchise) as a civil law contract for services has its place and role in the system of civil legal agree ments of the Republic of Kazakhstan.This paper reviewed the order and conditions of implementation, the place and importance in State regu lation, the legal function and improving the functions of the integrated businessentrepreneurial license (franchise) since its inception, provides recommendations to improve the Act of governing laws regulating the re lations of the complex enterprise license (franchise).